Tafsir Maqashidi atas Konsep "Al-'Ilm" dan "Al-Hikmah" dalam Al-Qur'an: Relevansinya dengan Pengembangan Sumber Daya Manusia dan Manajemen Pengetahuan di Lingkungan Society 5.0 - Moh. Bahrudin; Ahmad Nur Fathoni; Anwar Mukti; Agung Mandiro Cahyono; Luqman Hakim; Muhammad Burhanudin Nur Karim (Journal of Innovative and Creativity, 2021)
The research on Tafsir Maqashidi and Islamic epistemology explores the integration of higher objectives (maqashid) of the Qur'an with contemporary knowledge and human resource development (HRD) within Islamic frameworks. Studies highlight that Tafsir Maqashidi offers a purposive interpretation approach emphasizing spiritual, ethical, and intellectual dimensions, aligning revelation and reason as coequal knowledge sources, and promoting lifelong learning and moral responsibility in education. In HRD, Maqasid Sharia principles guide beyond skill enhancement to include spiritual and moral growth, fostering values-based personal and organizational development, as shown in waqf-based institutions and Islamic educational settings. The epistemological discourse also addresses the challenges of modern knowledge by integrating Islamic primary sources with reason and spirituality, offering alternative educational models responsive to contemporary societal needs. Additionally, Islamic philosophy’s concept of 'Ilm' (knowledge) provides a reflective knowledge framework valuable for knowledge management and learning organizations in the digital age. These findings imply that applying Maqashidi interpretation and Islamic epistemology can enrich knowledge management, HRD, and education in the context of Society 5.0, supporting holistic human development grounded in Islamic values.